Historical Perspectives on Exceptional Climatic Years at the Labrador/Nunatsiavut Coast 1780 to 1950 - Ouellet-Bernier, Marie-Michèle; De Vernal, Anne; Chartier, Daniel; Boucher, Étienne (Quaternary Research, 2021)
Abstract This interdisciplinary study presents a human perspective on climatic variations by combining documentary, discursive, instrumental, and proxy data. Historical sources were used to characterize climate variations along the coast of Labrador/Nunatsiavut during the 19 th century and the first half of the 20 th century. Written and early instrumental archives provided original information on the state and perception of climate before the establishment of meteorological stations, which permitted an intra-annual perspective on climatic variations. Written sources depicted the sensitivity of humans to climatic variations. Exceptional seasonal climatic events were extracted from documentary and discursive sources, which were complemented by tree-ring and early instrumental data. From 1780 to 1900, data indicated a succession of relatively warm and cold episodes. Most warm periods were described as stormy and variable. The final part of the studied records showed cold conditions from 1900 to 1925 and warm conditions from 1925 to 1950. Historical sources helped to discriminate a seasonal signal. Mild autumn-winter conditions were recorded since 1910 in relation with positive anomalies of the North Atlantic Oscillation in winter. Relatively warm spring-summer conditions were recorded after 1920, which corresponds to a phase of positive anomaly of the Atlantic Multidecadal Oscillation.

A database of Holocene temperature records for north‐eastern North America and the north‐western Atlantic - Van Bellen, Simon; De Vernal, Anne; To, Anna; Ouellet‐Bernier, Marie‐Michèle; Roy, Natasha; ClimHuNor Members (Geoscience Data Journal, 2020)
Abstract Centennial‐to‐millennial temperature records of the past provide a context for the interpretation of current and future changes in climate. Quaternary climates have been relatively well studied in north‐east North America and the adjacent Atlantic Ocean over the last decades, and new research methods have been developed to improve reconstructions. We present newly inferred reconstructions of sea surface temperature for the north‐western Atlantic region, together with a compilation of published temperature records. The database thus comprises a total of 86 records from both marine and terrestrial sites, including lakes, peatlands, ice and tree rings, each covering at least part of the Holocene. For each record, we present details on seasons covered, chronologies and information on radiocarbon dates and analytical time steps. The 86 records contain a total of 154 reconstructions of temperature and temperature‐related variables. Main proxies include pollen and dinocysts, while summer was the season for which the highest number of reconstructions were available. Many records covered most of the Holocene, but many dinocyst records did not extend to the surface, due to sediment mixing, and dendroclimate records were limited to the last millennium. The database allows for the exploration of linkages between sea ice and climate and may be used in conjunction with other palaeoclimate and palaeoenvironmental records, such as wildfire records and peatland dynamics. This inventory may also aid the identification of gaps in the geographic distribution of past temperature records thus guiding future research efforts.